Tinjauan Yuridis terhadap Transaksi Online oleh Anak di Bawah Umur Berdasarkan Hukum Positif Indonesia - Benny Benny; Finley Larissa Wilhelmina; Verina Tania Ruandi; Sonya Airini Batubara (Universitas Medan Area, 2020)
This article aims to see the development of online transactions that continue to cause new problems for the rule of law that has been established in a single jurisdiction. Problems that still arise are not only related to the preparation and evidence of contracts but also in other fields. There is a large amount of literature on how existing laws are currently being or might be developed, and how the parties to a contract solve the problems that might be caused by an invasion of online transactions. online transactions are new discovery transactions in the form of trade in which the seller and buyer do not encounter directly but only use the internet media. This study uses a normative juridical research method to address these online transactions operated by minors against the legal arrangement of the online trading system and legal protection mechanisms in which the results of this study indicate that the validity of minors is regulated in article 1320 of the Civil Code. Legal protection for legal events online transactions conducted by minors are racing against the electronic system agreed upon as regulated in article 19 of Act No. 19 of 2016 concerning Information on Electronic Transactions.